Correlation analysis of serum Glycosylphosphatidylinositol Mannosyltransferase 1 (GMP1) levels in type 2 diabetes mellitus: GMP1 in type 2 diabetes mellitus - Yang, Xiaolin; Wang, Qichang; Wei, Chen; Zhao, Jian (Journal of Medical Biochemistry, 2025)
Objective: To investigate the serum expression of Glycosylphosphatidylinositol Mannosyltransferase 1 (GMP1) in type 2 diabetes mellitus (T2DM) patients and its correlation with hypertriglyceridemia (HTG) to shed light on lipid metabolism disorders in T2DM. Methods: A total of 239 subjects were included, among whom 92 patients were in the T2DM combined with HTG group and 147 patients were in the T2DM without HTG group. The concentration of the serum GMP1 protein was quantitatively detected via enzyme-linked immunosorbent assay (ELISA). Moreover, the levels of serum triglycerides (TGs) and other related metabolic indicators (such as blood glucose, glycated hemoglobin (HbA1c), total cholesterol, and high/low-density lipoprotein cholesterol) were detected via conventional biochemical methods. To evaluate the potential impact of GMP1 on the occurrence of T2DM combined with HTG. Results: Both the DM group and the DM+HTG group had significantly higher serum GMP1 levels (P<0.01), and the GMP1 level in the DM+HTG group was considerably higher (P<0.05 or 0.01) than in the simple DM group. The serum GMP1 levels in T2DM and HTG patients were significantly higher. Serum GMP1 level (OR=1.527, 95% CI 1.200–1.943) were all determined by binary logistic regression analysis. 95% CI 1.003–1.010) was a separate risk factor for HTG and T2DM. Correlation analysis revealed that in patients with T2DM (especially those in the DM+HTG group). Multiple regression analysis further indicated that after controlling for factors such as age, sex, disease duration, BMI, and HbA1c, Higher blood GMP1 levels continued to be a predictor or independent factor for patients with T2DM complicated by HTG (P<0.05). Conclusion: Serum GMP1 levels are markedly elevated in T2DM patients, especially those with hypertriglyceridemia, and they are independently positively linked with triglycerides.